Translation and Gender in South America: The Representation of South American Women Writers in an Unequal Cultural Scenario - Ahumada-Figueroa, M; Campana-Garcia, A; Basaure-Cabero, R (Taylor and Francis, 2020)
Historically, translation has had a key role concerning cultural transfer. In the past few decades we have witnessed that within this process, the relation between translation and gender studies has become more evident and, therefore, it requires a deeper interdisciplinary analysis. What has been the historical significance of being a woman and writer in South American scenarios? When translated, what are the characteristics of texts written by women in countries that culturally establish polarized gender relations? How are power relations conceived in this context? This study analyzes the relation between gender representations and translation in South America and its historical and literary elements in the works of María Luisa Bombal and Silvina Ocampo as representatives of South American literature during the 20th century. The analysis focuses on the representations of female relations and experience in terms of body, motherhood, violence in the originals and English versions of their works. The discussion centres on the role of translation in revealing different linguistic, cultural, and ideological realities. © 2020 selection and editorial matter, Luise von Flotow and Hala Kamal; individual chapters, the contributors.